The internationalization of state-owned enterprises in liberalized markets: the role of home-country pro-market reforms - Santangelo, Grazia D.; Symeou, Pavlos C. (Journal of International Business Studies, 2024)
Abstract We study how home-country factors can alter the impact of host-country conditions on the location decisions of state-owned enterprises (SOEs). Specifically, we examine the role of home-country pro-market reforms in facilitating SOEs’ entry into host countries with a free-market logic. We consider two types of home-country pro-market reforms: market liberalization and privatization. We propose that home market liberalization mainly mitigates SOEs’ market legitimacy deficit and facilitates their entry into host countries with a prominent free-market logic. In such contexts, businesses perceive SOEs from more liberalized home markets as more accustomed to market competition and thus are less likely to exert pressure on the host government against them. We also argue that furthering SOEs’ privatization mitigates SOEs’ political legitimacy deficit in host countries with a free-market logic, thus facilitating entry. In these contexts, host governments perceive more privatized SOEs as more independent from their home state due to reduced political connections. We find support for our arguments in a dataset of 97 telecom SOEs from 97 countries over the period 1990–2010. Our study advances research on SOEs’ internationalization and research on pro-market reforms and has relevant implications for managers and policymakers.